1998
DOI: 10.1159/000054382
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine-Related Effects of Long-Term, ‘Binge’ Cocaine Administration: Diminished Individual Differences in Stress-Induced Corticosterone Response

Abstract: Acute cocaine administration activates behavioral and neuroendocrine processes associated with the stress response. However, much less is known about the effects of chronic, long-term cocaine administration on neuroendocrine adaptations and individual vulnerability to stress. We hypothesized that chronic ‘binge’ cocaine administration may serve as a chronic pharmacological stressor leading to a hyperactivity of the stress-responsive hypothalamic-pituitary-adrenal (HPA) axis and alterations in its feedback mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 38 publications
3
35
3
Order By: Relevance
“…In apparent contrast to the present data, a recent experiment by Sarnyai et al (1998) failed to detect differences in stress-induced levels of CORT following 60 min of restraint stress in rats that had been previously administered chronic cocaine, compared to control animals. In addition, their study observed increased levels of CORT in the cocaine-treated compared to the vehicle-treated animals in the non-stressed condition.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In apparent contrast to the present data, a recent experiment by Sarnyai et al (1998) failed to detect differences in stress-induced levels of CORT following 60 min of restraint stress in rats that had been previously administered chronic cocaine, compared to control animals. In addition, their study observed increased levels of CORT in the cocaine-treated compared to the vehicle-treated animals in the non-stressed condition.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, the augmented increases in CORT and ACTH that were observed in d-amphetamine pretreated rats in response to a drug challenge in the present study confirm the findings of Vanderschuren et al(1999), and also demonstrate that a more chronic schedule of d-amphetamine administration produces similar effects. Cross-sensitization of the HPA-axis between d-amphetamine and stress has been shown to occur when animals were initially exposed to different stressors, and then subjected to a d-amphetamine challenge , which is the converse of our novel findings.In apparent contrast to the present data, a recent experiment by Sarnyai et al (1998) failed to detect differences in stress-induced levels of CORT following 60 min of restraint stress in rats that had been previously administered chronic cocaine, compared to control animals. In addition, their study observed increased levels of CORT in the cocaine-treated compared to the vehicle-treated animals in the non-stressed condition.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In the animal literature, the effects of acute cocaine withdrawal on the HPA axis are consistent even when using different administration paradigms. For example, chronic cocaine exposure (15-45 mg/ kg/day) for 2 weeks has been reported to increase basal plasma CORT levels after 1 day of withdrawal (Borowsky and Kuhn, 1991;Levy et al, 1992;Sarnyai et al, 1998;Peltier et al, 2001;Zorrilla et al, 2001;Zhou et al, 2003;Picetti et al, 2010). Therefore, our present finding is consistent with and extends reports from other laboratories, demonstrating persistent HPA axis activation, with much longer duration after the cessation of chronic EDC.…”
Section: Hpa Hormonessupporting
confidence: 93%
“…Previous human and preclinical studies have shown that both acute (Mantsch et al 2003;Quiñones-Jenab et al 2000) short-term (Zhou et al 1999) and, in some cases, long-term (Sarnyai et al 1998) cocaine use culminates in increased progesterone and HPA axis activity. As such, secondary analysis was performed in the current study to investigate more clearly the impact of both cocaine consumption and abstinence on hormonal fluctuations first, by correlating drug consumption variables in the three months before in-patient entry with hormonal changes and second, by examining hormonal changes as a function of study day rather than MC day.…”
Section: Discussionmentioning
confidence: 99%